Internal flow structures in columnar jointed basalt from Hrepphlar, Iceland II: Magnetic anisotropy and rock magnetic properties ... - Almqvist, Bjarne S.G.; Bosshard, Sonja A.; Hirt, Ann Marie; Mattsson, Hannes B.; Hetényi, György (ETH Zurich, 2012)
Bulletin of Volcanology, 74 (7) ... : ISSN:0258-8900 ...